Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Geografi Melalui Pembelajaran Berbasis Lingkungan - Sudirman, Sudirman (UNIVERSITAS NEGERI MAKASSAR, 2020)
This research is a classroom action research that aims to increase student motivation in learning Geography through environment-based learning in class VII.D SMPN 40 Makassar. This research was conducted at SMPN 40 Makassar, where the research subjects were grade VII.D students, amounting to 35 people and the object of research was the environment around the school. This research was conducted in II (two) cycles. Data collection techniques used were the provision of tests and questionnaires at the end of each cycle and observation during the learning process. The results obtained are as follows: (1) From the results of the initial test it is categorized as moderate with an average value of 62.86; (2) The results of observation and reflection after the implementation of the first cycle shows that the category of student motivation in Geography subjects through environment-based learning has progressed from the medium category to high. In addition, the average value obtained increased from 62.86 to 67.68; (3) The results of observation and reflection after the implementation of the second cycle shows that students' motivation in Geography through environment-based learning has increased from the medium to high categories. In addition, the average value obtained increased from 67.68 to 81.07. From the results of the above analysis, the results of the action research revealed an increase in student motivation in Geography subjects through environment-based learning before implementing the action and after implementing the action.